The direct contact condensation of steam on a water spray - Evangelos V. Kaimakamis (1984)
Direct contact spray condensers are effective devices for heat and mass transfer. They are characterized as low cost, low pressure drop equipment, and to their advantage could be added the ability to handle corrosive vapour mixtures, simplicity of construction, compactness, adaptability, ease of control and absence of fouling problems. [Continues.]